Spór wokół projektu przekształcenia Pensylwanii w kolonię królewską (1764-1765) - Daszynska, Jolanta (Acta Universitatis Lodziensis. Folia Historica, 1995)
Pennsylvania founded in 1681 was the private colony. It belonged to William Penn and after his death to his heirs. It was one of the most populous and rich colony dominated by Quakers. Both they and many other people according to the charter of privileges had their political and religious rights and liberties. But yet in 1703 W. Penn wanted to sold his colony to the Crown. Some other atemptions were made next years. The Penn family who lived in England were attacked and criticized both in England and also in their colony. So the idea of the change of government was stronger and stronger. After the Seven Years War the Pennsylvania Assembly and mainly Joseph Galloway and Bejnamin Franklin were the persons, who once again proposed the idea of royal colony. In their opinion the Pennsylvania charter of privileges would not be changed, but the Penn family would loose their rights as the proprietors. They would be only the landlords. On the other side John Dickinson and the Proprietary Party wanted to show the disadvantages of such change. Their most important argument was that the rights and privileges of the inhabitants would be changed. Under the strong influence of B. Franklin and J. Galloway the Pennsylvania Assembly voted the petition for a change of government (may 1764). It was to be sent to the king and B. Franklin was appointed an agent to support the petition in London. The Board of Trade rejected this petition in 1765. Pennsylvania remained the private colony till the end of colonial days.